Desenvolvimento e caracterização de um smart wound dressing: membrana de colágeno com propriedade antimicrobiana e monitoramento bacteriano - Alves, Gabriella Monteiro (Universidade Federal de São Carlos, 2025)
Burns are complex and severe injuries that affect the skin and, in severe cases, deeper tissues, potentially leading to complications such as infections and prolonged healing. The treatment of burns with conventional dressings can cause additional injuries due to their adherence to the tissue. Collagen (COL) is widely used in the biomedical field for its regenerative properties and can aid in burn healing. However, it has limitations such as low mechanical strength and rapid biodegradability. To overcome these limitations, COL can undergo crosslinking processes, for which vanillin (VAN) was used in this study, resulting in a material with improved physical properties. To develop an intelligent membrane capable of detecting pH changes, red cabbage extract (RCE) was incorporated into the COL membrane crosslinked with VAN. The methodology for the development and characterization of the membrane included the extraction and lyophilization of anthocyanins from red cabbage, as well as the formation of COL, COL/RCE, COL/VAN (0.5%, 1%, 3%, and 6% vanillin), and COL/RCE/VAN (0.5%, 1%, 3%, and 6% vanillin) membranes. SDS-PAGE electrophoresis analysis confirmed that the COL used in membrane preparation corresponds to type I collagen. Although the smart wound dressing exhibited lower mechanical properties compared to COL, techniques such as Scanning Electron Microscopy (SEM), Fourier Transform Infrared Spectroscopy (FTIR), Thermogravimetry (TG), Differential Scanning Calorimetry (DSC), and Proton Nuclear Magnetic Resonance Spectroscopy (¹H NMR) demonstrated that RCE and a 6% VAN concentration increased the crosslinking of COL, improving its stability and thermal properties. The membranes containing RCE exhibited lower swelling, indicating higher crosslinking. Furthermore, RCE was not negatively affected by COL and VAN in its pH indicator capability. VAN at 6% demonstrated an antimicrobial effect, and the membranes containing ERR proved effective in detecting the presence of bacteria. The influence study of RCE variation indicated that VAN is essential for the structural and functional stability of the membranes, as well as for promoting COL crosslinking. Thus, the COL/RCE/6% VAN membrane has the potential to be used as a wound dressing to monitor the condition of injuries such as burns, indicate the presence of bacterial infections in the wound, and offer a low-cost solution.
Development and characterization of a smart wound dressing: collagen membrane with antimicrobial properties and bacterial monitoring
Keywords: Colágeno; Extrato de Repolho Roxo; Indicador de pH; Reticulação; Vanilina; Queimaduras de Segundo Grau; Collagen; Red Cabbage Extract; pH Indicator; Crosslinking; Vanillin; Second Degree Burns; ENGENHARIAS::ENGENHARIA BIOMEDICA::ENGENHARIA MEDICA::BIOMATERIAIS E MATERIAIS BIOCOMPATIVEIS